Synthesis, characterization, and antiproliferative effect of CuO-TiO2-chitosan-Amygdalin nanocomposites in human leukemic MOLT4 cells - Elderdery, Abozer Y.; Alzahrani, Badr; Hamza, Siddiqa M. A.; Hedeab, Gomaa Mostafa; Mok, Pooi Ling; Subbiah, Suresh Kumar (Hindawi, 2022)
The main aim of this study was to synthesize copper oxide- (CuO-) titanium oxide- (TiO2-) chitosan-amygdalin nanocomposites (CTCANc) and to characterize them physically and biologically (antimicrobial and anticancer activity using MOLT4 blood cancer cell line) to endorse their useful applications as potential drug candidates in anticancer avenues. CuO-TiO2-chitosan-amygdalin nanocomposites were synthesized according to standard, reported methods. Physical characterization of the nanocomposites was performed using methods like X-ray diffractometer (XRD), and morphological and ultrastructural analysis of nanocomposites were done using electron microscope scanning and transmission. FTIR was recorded using a Perkin-Elmer spectrometer, and photoluminescence (PL) spectra were done using the spectrometer. Further, antibacterial activities were assessed using standard bacterial cultures. To demonstrate the nanocomposite’s anticancer effects, MTT assay, morphological analysis, apoptosis studies using acridine orange/ethidium bromide (AO/EtBr) dual staining, reactive oxygen species (ROS) analysis, and levels of antioxidant enzymes were analyzed using the MOLT4 blood cancer cell line. Synthesized nanocomposites were characterized using XRD and showed various peaks, respectively, for CuO-TiO2, amygdalin, and chitosan. MTT assay indicated an IC50 value of 38.41 μg/ml concentration of CTCANc. Hence, 30 and 40 μg/ml were used for the subsequent experiments. Morphological analysis, staining for apoptosis using AO/EtBr, mitochondrial membrane potential (MMP or ΔΨm) analysis, ROS analysis, and determination of the SOD, CAT, MDA, and GSH levels were performed. Observations like a significant loss of morphology, induction of apoptosis, elevated ROS, and decreased MMP were significant in 30 and 40 μg/ml nanocomposite-treated cells when compared to control cells. The bimetallic nanocomposites exhibited typical nanocomposites characteristics and significant antibacterial and anticancer effects. The study results endorse the antibacterial, anticancer activity of CuO-TiO2-chitosan-amygdalin nanocomposites and strongly suggest that further in-depth research using CuO-TiO2-chitosan-amygdalin nanocomposites could reveal their efficacy in the clinical scenario.